Current use of cardiac magnetic resonance in tertiary referral centres for the diagnosis of cardiomyopathy: the ESC EORP Cardiomyopathy/Myocarditis Registry. (8th January 2021) - Mizia-Stec, Katarzyna; Charron, Philippe; Gimeno Blanes, Juan Ramon; Elliott, Perry; Kaski, Juan Pablo; Maggioni, Aldo P; Tavazzi, Luigi; Tendera, Michał; Felix, Stephan B; Dominguez, Fernando; Ojrzynska, Natalia; Losi, Maria-Angela; et al.
Abstract: Aims : Cardiac magnetic resonance (CMR) is recommended in the diagnosis of cardiomyopathies, but it is time-consuming, expensive, and limited in availability in some European regions. The aim of this study was to determine the use of CMR in cardiomyopathy patients enrolled into the European Society of Cardiology (ESC) cardiomyopathy registry [part of the EURObservational Research Programme (EORP)]. Methods and results : Three thousand, two hundred, and eight consecutive adult patients (34.6% female; median age: 53.0 ± 15 years) with cardiomyopathy were studied: 1260 with dilated (DCM), 1739 with hypertrophic (HCM), 66 with restrictive (RCM), and 143 with arrhythmogenic right ventricular cardiomyopathy (ARVC). CMR scans were performed at baseline in only 29.4% of patients. CMR utilization was variable according to cardiomyopathy subtypes: from 51.1% in ARVC to 36.4% in RCM, 33.8% in HCM, and 20.6% in DCM ( P  < 0.001). CMR use in tertiary referral centres located in different European countries varied from 1% to 63.2%. Patients undergoing CMR were younger, less symptomatic, less frequently had implantable cardioverter-defibrillator (ICD)/pacemaker implanted, had fewer cardiovascular risk factors and comorbidities ( P  < 0.001). In 28.6% of patients, CMR was used along with transthoracic echocardiography (TTE); 67.6% patients underwent TTE alone, and 0.9% only CMR. Conclusion : Less than one-third of patients enrolled in the registry underwent CMR and the use varied greatly between cardiomyopathy subtypes, clinical profiles of patients, and European tertiary referral centres. This gap with current guidelines needs to be considered carefully by scientific societies to promote wider availability and use of CMR in patients with cardiomyopathies. Graphical Abstract: